“Voroshilov ,s Commission” the leavning structure of soviet planning for Germany during the Great Patriotic war - A. M. Filitov (Vestnik MGIMO-Universiteta)
The article deals with the planning activities of the “Armistice Commission” set up under the auspices of the Soviet Commissariat of the Foreign Affairs in September 1943. Headed by Marshal Voroshilov it played a crucial role in working-out the terms of unconditional surrender of Germany which aimed at the creation of a demilitarized, de-nazified democratic German state.